1976
DOI: 10.1177/000348947608500508
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Tracheoesophageal Fistulas in Adults

Abstract: Congenital tracheoesophageal fistula without esophageal atresia is commonly known as "H" type. This is an extremely rare anomaly in infants and accounts for approximately 1 1/2-4% of all congenital tracheoesophageal malformations. An anomaly should be described by its anatomical defect, not by a number or letter. There are five main anatomical categories with 85-95% being of the esophageal atresia and distal tracheoesophageal fistula type. About 1 1/2% are of the "H" type. Although today tracheoesophageal fist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Heitmiller et al [12] reported detailed esophageal manometric findings as uncoordinated, lowamplitude peristalsis of the esophageal body; both low and normal LES pressures in an adult with congenital Htype TEF, with persisting manometric findings after fistula repair. Esophageal dysmotility has also been reported in a child and few adults with H-type TEF [3,4,7]. Additionally, it is possible that an esophagus which has been periodically distended with air for long time may show dysmotility [4].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Heitmiller et al [12] reported detailed esophageal manometric findings as uncoordinated, lowamplitude peristalsis of the esophageal body; both low and normal LES pressures in an adult with congenital Htype TEF, with persisting manometric findings after fistula repair. Esophageal dysmotility has also been reported in a child and few adults with H-type TEF [3,4,7]. Additionally, it is possible that an esophagus which has been periodically distended with air for long time may show dysmotility [4].…”
Section: Discussionmentioning
confidence: 99%
“…1 a Chest X-ray demonstrating dilated esophagus (arrows) and bronchiectatic areas. b HRCT revealing bronchiectatic areas adulthood [1][2][3][4][5]. The classical triad of symptoms is paroxysmal choking and cough precipitated by feeds, abdominal distention due to passage of air from the trachea to the esophagus and recurrent aspiration pneumonia [1,7,9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is known that some of these cases remain undiagnosed until adulthood, the oldest reported case being 63 years of age. [22][23] The diagnosis of these fistulas should be made by barium swallow with cinefluoroscopy and video recording, as they can be missed by the conventional methods such as esophagography. 24 Tracheobronchoscopy in conjunction with instillation of methylene blue into the esophagus to identify the tracheoesophageal fistula was recommended by Abbott.…”
Section: Discussionmentioning
confidence: 99%